Meiotic Recognition of Evolutionarily Diverged Homologs: Chromosomal Hybrid Sterility Revisited. (8th April 2023) - Forejt, Jiri; Jansa, Petr
Abstract: Hybrid sterility (HS) is an early postzygotic reproductive isolation mechanism observed in all sexually reproducing species. Infertility of hybrids prevents gene flow between incipient species and leads to speciation. While Drosophila studies have focused almost exclusively on the genic control of HS, two other model species, Mus musculus and budding yeast, provided the first experimental evidence of hybrid sterility governed by the nongenic effects of DNA sequence divergence. Here, we propose that the nongenic effect of increasing DNA divergence between closely related species may impair mutual recognition of homologous chromosomes and disrupt their synapsis. Unsynapsed or mispaired homologs can induce early meiotic arrest, or their random segregation can cause aneuploidy of spermatids and sperm cells. Impaired recognition of homologs may thus act as a universal chromosomal checkpoint contributing to the complexity of genetic control of HS. Chromosomal HS controlled by the Prdm9 gene in mice and HS driven by the mismatch repair machinery in yeast are currently the most advanced examples of chromosomal homology search-based HS. More focus on the cellular and molecular phenotypes of meiosis will be needed to further validate the role of homolog recognition in hybrid sterility and speciation.